Análisis del problema de contención en OBS (Optical Burst Switching) (2010)
In this document was realized an analysis of contention problem in optical burst switched networks (OBS), whose main objective was to analyze the impact of offset time in the resolution of OBS contention, taking into account two contention resolution techniques: burst segmentation and wavelength conversion. It was used the simulation tool NCTUns version 6.0 under the operating system Fedora 11. The results indicated that varying the offset time on different contention resolution techniques presented in this document, there was effect on throughput, delay and loss rate of the network.